Coating material finishing composition and coating material finishing method
The coating material composition effectively replicates the straw grass clay wall texture by using fine titanium oxide and zinc oxide to maintain straw visibility and enhance weather resistance, addressing design and durability issues in existing technologies.
Patent Information
- Application Number
- JP2023092094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Existing coating materials fail to accurately replicate the straw grass clay wall texture due to the use of synthetic fibers, which can expose synthetic fibers on the surface, and colored straw compositions may be hidden by other materials, leading to poor design and weather resistance issues.
A coating material composition comprising an acrylic resin emulsion, filler, aggregate, straw, fine titanium oxide and/or zinc oxide, and a thickener, with specific particle sizes and ratios to maintain straw visibility and enhance weather resistance.
The composition provides a decorative appearance resembling a straw-covered earthen wall, maintains design integrity, and offers excellent weather resistance, while improving the coating film's strength and crack resistance.
Smart Images

Figure 2024174332000001 
Figure 2024174332000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating material finishing composition and a coating material finishing method that can give the exterior wall of a building a design resembling an earthen wall containing straw (hereinafter, referred to as a straw-suna earthen wall design). [Background technology]
[0002] Patent Document 1 discloses a straw fiber-like coating composition that contains 5 to 100 parts by weight of monofilament synthetic fibers with a fiber length of 2 to 20 mm and a fiber diameter of 0.1 to 2 mm, and 50 to 1,000 parts by weight of powder with a particle diameter of 0.01 to 2 mm, per 100 parts by weight of synthetic resin emulsion solids, with the ratio of the average fiber diameter of the synthetic fibers to the average particle diameter of the powder being in the range of 1:5 to 5:1.
[0003] Furthermore, Patent Document 2 discloses a coating material containing colored straw, which is characterized by being made by mixing colored straw that has been colored to produce shades using a coloring agent containing a solvent, resin, and pigment, with aggregate and a binder resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-302575 [Patent Document 2] JP 2006-037041 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the straw fiber-like paint composition described in Patent Document 1 uses synthetic fibers instead of straw, which can result in a design that differs from the straw-like earthen wall look. Also, when the synthetic fibers are partially exposed on the coating surface, the non-straw material can create an aesthetic that is even more different from the straw-like earthen wall look.
[0006] In addition, the colored straw-containing coating material described in Patent Document 2 has the problem that the colored straw may be concealed by other materials, resulting in poor design. In addition, when a pigment such as titanium oxide is added to ensure sufficient weather resistance, the colored straw may be further concealed, resulting in poor design.
[0007] The problem that the present invention aims to solve is to provide a coating material finishing composition and coating material finishing method that use straw and can achieve a high level of straw-like earthen wall look because the straw is not hidden by other materials, and that has excellent weather resistance. [Means for solving the problem]
[0008] In order to solve the above problems, the invention described in claim 1 is a composition comprising an acrylic resin emulsion, a filler, an aggregate, straw, a pigment, a thickener, and a film-forming aid, The present invention provides a coating finishing composition, characterized in that the pigment contains fine titanium oxide and / or fine zinc oxide having a primary particle diameter of 10 to 100 nm, and the total amount of the fine titanium oxide and / or fine zinc oxide is 0.5 to 4.5 parts by weight per 100 parts by weight of the total composition.
[0009] The invention described in claim 2 provides the coating finishing composition described in claim 1, characterized in that the straw is contained in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the entire composition.
[0010] The invention described in claim 3 provides the coating finishing composition described in claim 1 or 2, characterized in that the length of the straw is 1 to 100 mm.
[0011] The invention described in claim 4 is a method of applying a sealer onto or over a base and drying it, and then: The undercoat material composition is characterized in that it contains an acrylic resin emulsion, a filler, an aggregate, a pigment, a thickener, and a film-forming aid, and the blending amount of the pigment is 0.5 to 5.0 parts by weight per 100 parts by weight of the composition, and is applied in an amount of 0.7 to 1.5 kg / m2 Apply and let dry. On top of this, the coating material finishing composition according to any one of claims 1 to 3 is applied in an amount of 1.0 to 5.0 kg / m 2 The present invention provides a coating material finishing method, which is characterized by applying the coating material by using a coating method. Effect of the Invention
[0012] The coating material finishing composition of the present invention has the effect that the straw used to impart design is not concealed, and therefore the exterior wall of the building can be made to look like a straw-like clay wall. The inventors have repeatedly conducted trial and error and experiments to solve the above-mentioned problems, and as a result, have discovered that by using fine particles of titanium oxide and / or fine particles of zinc oxide as pigments, instead of general titanium oxide or zinc oxide, the straw mixed in the coating material finishing composition is not concealed, and a coating material finish with excellent aesthetics without impairing design properties can be provided. Fine particles of titanium oxide and / or fine particles of zinc oxide have a smaller primary particle diameter than general ones, so it is believed that the light scattering is small and the transparency is high, and this is why the straw is not concealed.
[0013] In addition, the coating finishing composition of the present invention has the effect of being excellent in weather resistance, which inhibits discoloration and deterioration of the coating film, and therefore has the effect of maintaining the beauty of the coating immediately after application for a long period of time.
[0014] In addition, the coating material finishing composition of the present invention contains straw to obtain a straw-like earthen wall look, and the straw also contributes to improving the strength of the coating film. This has the effect of having a base-following property that allows the coating film to follow vibrations caused by earthquakes, wind pressure, and vehicle passage, as well as cracks in the base caused by such vibrations, and has the effect of making the coating film less likely to crack or peel off.
[0015] The coating method described in claim 4 has the effect of not concealing the straw, as described above, and the straw-like mud wall finish applied to the wall of a building by the coating method has the effect of being highly aesthetic. In addition, since the coating method uses an undercoat coating composition and a coating finish composition containing an acrylic resin emulsion as a binder, the hardened coating film is flexible and can follow vibrations caused by earthquakes, wind pressure, and vehicle passage of the building, as well as cracks in the base caused by the vibrations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described in detail below.
[0017] First, the coating material finishing composition of the present invention and the undercoat material composition used in the coating material finishing method of the present invention will be described.
[0018] The coating material finishing composition of the present invention is a composition containing an acrylic resin emulsion, a filler, an aggregate, a straw, a pigment, a thickener, and a film-forming aid, and the pigment contains fine titanium oxide and / or fine zinc oxide having a primary particle diameter of 10 to 100 nm, and the total amount of fine titanium oxide and / or fine zinc oxide is 0.5 to 4.5 parts by weight in 100 parts by weight of the entire composition. The undercoat material composition used in the coating material finishing method of the present invention contains an acrylic resin emulsion, a filler, an aggregate, a pigment, a thickener, and a film-forming aid, and the amount of pigment is 0.5 to 5.0 parts by weight in 100 parts by weight of the composition. These can also be blended with defoamers, preservatives, dispersants, anti-algae and anti-fungal agents, and antifreeze agents that are generally used in aqueous compositions.
[0019] <Acrylic resin emulsion> The acrylic resin emulsion constituting the undercoat material composition used in the coating material finishing composition of the present invention and the coating material finishing method of the present invention can be an acrylic resin emulsion such as an acrylic acid ester copolymer resin, a vinyl acetate-acrylic acid ester copolymer resin, or a silicon-modified acrylic resin. The acrylic monomers that make up the acrylic resin include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, t-butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, nonyl acrylate, decyl acrylate, dodecyl acrylate, n-amyl acrylate, isoamyl acrylate, lauryl acrylate, stearyl acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, and isobutyl (meth)acrylate. butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate, and the like can be used.
[0020] Other unsaturated monomers include styrene derivatives such as styrene, α-methylstyrene, chlorostyrene, vinyltoluene, and methoxystyrene; carboxyl group-containing monomers such as (meth)acrylic acid, fumaric acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, and crotonic acid; (meth)acrylic acid, crotonic acid, and itaconic acid; 2-hydroxyethyl (meth)acrylate, 2(3)-hydroxypropyl (meth)acrylate, 4-hydroxybutyl acrylate, allyl alcohol, and polyhydric Hydroxyl group-containing monomers such as mono(meth)acrylic acid esters of alcohols; amide group-containing monomers such as (meth)acrylamide and maleinamide; amino group-containing monomers such as 2-aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, 3-aminopropyl(meth)acrylate, 2-butylaminoethyl(meth)acrylate, and vinylpyridine; glycidyl(meth)acrylate, allyl glycidyl ether, epoxy compounds having two or more glycidyl groups, and compounds having active hydrogen atoms. Epoxy group-containing monomers and oligomers obtained by reacting with ethylenically unsaturated monomers having the following structure: vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxyethyltrimethoxysilane, 2-(meth)acryloxyethyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane Alkoxysilyl group-containing monomers such as silane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropylmethyldipropoxysilane, 3-(meth)acryloxybutylphenyldimethoxysilane, 3-(meth)acryloxypropyldimethylmethoxysilane, and 3-(meth)acryloxypropyldiethylmethoxysilane; and other monomers that can be used include vinyl acetate, vinyl chloride, and further ethylene, butadiene, acrylonitrile, and dialkyl fumarate.
[0021] The glass transition temperature of the resin in the acrylic resin emulsion is preferably -30 to 40 ° C. If the glass transition temperature is less than -30 ° C, tack may occur on the finished surface and it may become easily dirty, and if it is more than 40 ° C, film formation may be poor. The glass transition temperature here is a value measured by a differential scanning calorimetry (DSC). The resin solid content is preferably 5.0 to 25.0 parts by weight in the total 100 parts by weight of the coating material finishing composition of the present invention, and if it is less than 5.0 parts by weight, adhesion and application workability may decrease, and if it exceeds 25.0 parts by weight, the viscosity may decrease and application workability may decrease. In addition, 7.0 to 27.0 parts by weight in the total 100 parts by weight of the undercoat material composition is preferably 7.0 to 27.0 parts by weight, and if it is less than 7.0 parts by weight, adhesion and application workability may decrease, and if it exceeds 27.0 parts by weight, the viscosity may decrease and application workability may decrease. Commercially available acrylic resin emulsions include Acronal 7059 (solid content: 55% by weight, glass transition temperature of resin: 30°C, copolymer of styrene, acrylic ester, and methacrylic ester, manufactured by BASF, product name) and Acronal YJ6235D (solid content: 55%, glass transition temperature of resin: 6°C, copolymer of styrene and acrylic ester, manufactured by BASF, product name).
[0022] <Filling material> The filler constituting the coating material finishing composition of the present invention and the undercoat material composition used in the coating material finishing method of the present invention has an average particle size D 50The filler has a particle size of less than 100 μm (50% cumulative particle size by weight), and is blended for the purpose of adjusting the viscosity and application workability of the composition. Heavy calcium carbonate, clay, kaolin, talc, precipitated barium sulfate, barium carbonate, silica sand powder, etc. can be used, and heavy calcium carbonate is inexpensive and can reduce the cost burden (pigments are excluded from the filler). The amount of filler blended is preferably 3 to 20 parts by weight, more preferably 4 to 12 parts by weight, out of 100 parts by weight of the total coating material finishing composition. If it is less than 3 parts by weight, the hiding power is insufficient, such as the color of the base being visible, and if it exceeds 20 parts by weight, the viscosity may increase and the application workability may be poor, if it is less than 4 parts by weight, the hiding power may decrease depending on the color tone, and if it exceeds 12 parts by weight, the application workability in low temperature environments such as winter tends to decrease. In addition, it is preferably 5 to 15 parts by weight, more preferably 8 to 12 parts by weight, out of 100 parts by weight of the total undercoat material composition. If it is less than 5 parts by weight, the hiding power will be insufficient and the color of the base will show through, if it exceeds 15 parts by weight, the viscosity will be too high and application workability may be poor, if it is less than 8 parts by weight, the hiding power may decrease depending on the color tone, and if it exceeds 12 parts by weight, application workability in low temperature environments such as winter tends to decrease.
[0023] <Aggregate> The aggregate constituting the coating material finishing composition of the present invention and the undercoat material composition used in the coating material finishing method of the present invention has an average particle size D 50The aggregate is preferably 40 to 60 parts by weight out of 100 parts by weight of the total coating composition. If the aggregate is less than 40 parts by weight, the design (the unevenness of the coating) may be insufficient, and if the aggregate is more than 60 parts by weight, the coating workability may be reduced. In addition, 25 to 45 parts by weight per 100 parts by weight of the total primer composition is preferable; if it is less than 25 parts by weight, the design (uneven feel of the coating material) may be insufficient, and if it exceeds 45 parts by weight, application workability may decrease.
[0024] <Straw> The straw that constitutes the coating material finishing composition of the present invention is blended for the purpose of obtaining a straw-like earthen wall design. In addition, by blending fibrous straw, it is expected that the crack tracking ability can be improved. Straw is straw used as a material for earthen walls, and there are rough straw, which is simply cut straw, and kneaded straw, which is kneaded before use. In the present invention, rough straw and kneaded straw can be used, and they may be used together. In addition, straw that has been de-blanched is preferable, and if it is used without de-blanching, the resin may not harden properly. The length of the straw is preferably 1 to 100 mm, more preferably 5 to 70 mm, and even more preferably 10 to 50 mm. If it is less than 1 mm, the design of the straw-like earthen wall may be inferior, and if it exceeds 100 mm, the application workability may be poor. The amount of straw is preferably 0.01 to 10 parts by weight, more preferably 0.05 to 8 parts by weight, per 100 parts by weight of the entire coating material finishing composition. If it is less than 0.01 part by weight, the design of the straw clay wall may be poor, if it exceeds 10 parts by weight, the application workability may be poor, if it is less than 0.05 parts by weight, depending on the design that requires thick application and construction, the straw may be buried and the straw clay wall may not be obtained, if it exceeds 8 parts by weight, the application workability may be poor in low temperature environments such as winter. Examples of commercially available straw include Warasei Warasa (length: 30 to 50 mm, Warasei Murai Shoten, product name) and Akunukisusa (length: 10 to 20 mm, Kinki Wall Materials Industry Co., Ltd., product name).
[0025] <Pigments> The coating material finishing composition of the present invention contains fine titanium oxide and / or fine zinc oxide as pigments, which have a primary particle diameter of approximately 200 nm or more, which is smaller than that of general coating materials. In the present invention, fine titanium oxide and / or fine zinc oxide are used for the purpose of preventing the other materials in the coating material finishing composition from concealing the straw when the straw is mixed into the coating material finishing composition, and preventing the design from being impaired. They are also used for the purpose of improving weather resistance. Since fine titanium oxide and / or fine zinc oxide have a small particle diameter, the scattering efficiency of visible light is minimized, making them more transparent than general titanium oxide and zinc oxide, and it is presumed that the coating material finishing composition of the present invention also has the effect of not concealing the straw due to the transparency.
[0026] Fine particle titanium dioxide may be surface-treated with inorganic systems such as zirconium hydroxide or aluminum hydroxide, with organic systems such as stearic acid or lauric acid, or with a combination of inorganic and organic systems. Since inorganic surface-treated titanium dioxide is hydrophilic and organic surface-treated titanium dioxide is water-repellent, it is preferable to use hydrophilic titanium dioxide that has been surface-treated with an inorganic system in the coating finishing composition of the present invention in order to improve dispersibility.
[0027] The primary particle diameter of the fine titanium oxide and / or fine zinc oxide used in the coating material finishing composition of the present invention is preferably 10 to 100 nm, more preferably 10 to 50 nm. If the primary particle diameter is less than 10 nm, dispersibility may decrease, and if it exceeds 100 nm, transparency may decrease and straw may be concealed. The amount of the fine titanium oxide and / or fine zinc oxide is preferably 0.5 to 4.5 parts by weight in 100 parts by weight of the total coating material finishing composition, and if it is less than 0.5 parts by weight, weather resistance may be insufficient, and if it exceeds 4.5 parts by weight, straw may be concealed. Commercially available products of fine titanium oxide that can be used in the coating material finishing composition of the present invention include TTO-55(D) (surface treatment: zirconium hydroxide / aluminum hydroxide, primary particle diameter: 30 to 50 nm, manufactured by Ishihara Sangyo Kaisha, Ltd., product name), and commercially available products of fine zinc oxide include FZO-50 (primary particle diameter: 21 nm, manufactured by Ishihara Sangyo Kaisha, Ltd., product name).
[0028] In addition to fine titanium oxide and / or fine zinc oxide, inorganic pigments such as carbon black, ferric oxide (red oxide), lead chromate, yellow lead, and yellow iron oxide can be used as pigments in the coating material finishing composition of the present invention. In addition, ordinary titanium oxide or zinc oxide with a large particle size may be used to color it white, but as mentioned above, ordinary titanium oxide or zinc oxide may hide the straw, so the amount of blending is limited to a small amount. Specifically, it is preferable that the amount of blending is less than 3.0 parts by weight in 100 parts by weight of the entire coating material finishing composition.
[0029] The pigment constituting the undercoat material composition used in the coating material finishing method of the present invention can be inorganic pigments such as titanium oxide, zinc oxide, carbon black, ferric oxide (red oxide), lead chromate, yellow lead, yellow iron oxide, etc., among which titanium oxide has excellent hiding power of the base and can be used as the main pigment for imparting hiding power because it is white. As the titanium oxide, general titanium oxide can be used, and those with a primary particle diameter of more than 200 nm are preferable. The blending amount is preferably 0.5 to 5.0 parts by weight in 100 parts by weight of the total undercoat material composition, and if it is less than 0.5 parts by weight, the base hiding power may be insufficient, and if it is more than 5.0 parts by weight, the coating workability may be poor. By the pigment contained in the undercoat material composition being within the above range, the base is well hidden, and even if the coating material finishing composition is applied on top of it, the base does not show through, and a finish with excellent design can be obtained.
[0030] <Thickener> The thickener constituting the undercoat material composition used in the coating material finishing method of the present invention and the coating material finishing composition of the present invention is blended for the purpose of improving trowel application workability and water retention, and water-soluble cellulose ether, urethane-modified polyether, polycarboxylic acid, etc. can be used. As the water-soluble cellulose ether, there is hi-metolose 90SH-15000 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name). The blending amount of the thickener is preferably 0.1 to 5.0 parts by weight per 100 parts by weight of the total composition. If it is less than 0.1 part by weight, sufficient thickening effect cannot be obtained, and sagging may occur during application, resulting in poor workability. If it exceeds 5.0 parts by weight, it may become heavy when applied with a trowel, and clogging may occur when applied with a spray gun for architectural coating materials.
[0031] <Film-forming aid> The coating material finishing composition of the present invention and the undercoat material composition used in the coating material finishing method of the present invention are blended with the film-forming aid for the purpose of promoting the fusion of the polymer particles of the emulsion and forming a uniform film by the polymer, and ethylene glycol diethyl ether, benzyl alcohol, butyl cellosolve, ester alcohol, etc. can be used. The blending amount of the film-forming aid is preferably 0.5 to 10 parts by weight in 100 parts by weight of the total composition, and if it is less than 0.5 parts by weight, film formation at low temperatures may be insufficient, and if it exceeds 10 parts by weight, dirt may easily adhere to the surface of the coating material.
[0032] In addition to the above, it is preferable that the coating material finishing composition of the present invention and the undercoat material composition used in the coating material finishing method of the present invention contain antifoaming agents, preservatives, dispersants, anti-algae and anti-fungal agents, and antifreeze agents that are generally used in aqueous compositions.
[0033] The viscosity of the coating material finishing composition of the present invention is preferably 400 to 800 Pa·s, and if it is less than 400 Pa·s, sagging may occur and the design may be impaired, and if it exceeds 800 Pa·s, application workability may be poor. If the viscosity increases due to low air temperature, more than 0 parts by weight and 15 parts by weight or less of water may be added to 100 parts by weight of the coating material finishing composition of the present invention to adjust the viscosity to the above range.
[0034] Next, the coating material finishing method of the present invention will be described.
[0035] The coating material finishing method of the present invention involves applying a sealer on or above a base, drying the sealer, and then applying an undercoat material composition containing an acrylic resin emulsion, a filler, an aggregate, a pigment, a thickener, and a film-forming aid, the pigment content of which is 0.5 to 5.0 parts by weight per 100 parts by weight of the composition, at an application rate of 0.7 to 1.5 kg / m. 2 and drying, and then the coating material finishing composition according to any one of claims 1 to 3 is applied thereon in an amount of 1.0 to 5.0 kg / m 2The undercoat composition and the coating finish composition can contain defoamers, preservatives, dispersants, anti-algae and anti-fungal agents, and antifreeze agents that are generally used in aqueous compositions.
[0036] The coating material finishing method of the present invention can be applied to mortar substrates, concrete substrates, precast concrete panel (PC panel) substrates, autoclave-cured lightweight aerated concrete panel (ALC panel) substrates, ceramic siding substrates, and painted substrates, and the painted substrates include acrylic resin-based, acrylic urethane resin-based, polyurethane resin-based, fluororesin-based, silicone acrylic resin-based, vinyl acetate resin-based, and epoxy resin-based coatings. In order to ensure sufficient adhesion, a sealer suitable for each substrate can be applied, but if the adhesion between the substrate and the undercoat composition used in the coating material finishing method of the present invention is sufficient when directly applied to the substrate, a sealer is not required. Examples of usable sealers include JS-800 (water-based acrylic resin sealer, manufactured by Aica Kogyo Co., Ltd., product name), JS-410 (solvent-based chlorinated rubber-based undercoat material, manufactured by Aica Kogyo Co., Ltd., product name), and JS-90 (water-based acrylic resin-based undercoat material, manufactured by Aica Kogyo Co., Ltd., product name).
[0037] A trowel, roller, or a spray gun for architectural coating materials with a diameter of 4 to 8 mm can be used to apply the undercoat composition used in the coating material finishing method of the present invention. Depending on the painting tool, the thickness of the coating may not be thick enough and the base hiding power may be insufficient, but in that case, it is recommended to apply the composition two or more times in succession after drying. In addition, a trowel or a spray gun for architectural coating materials with a diameter of 8 to 14 mm can be used to apply the coating material finishing composition of the present invention. A metal trowel made of stainless steel with a thickness of 0.3 to 0.7 mm is preferable because it can be applied with good workability. Since the size of the particles of the composition sprayed by the architectural coating material spray gun changes depending on the size of the diameter, and the design obtained changes, the size of the diameter appropriate for forming the desired design is appropriately selected. There are various types of spray guns for architectural coating materials, such as gravity type, suction type, and pressure type, and all of them can be used in the present invention, and the gravity type, which is less likely to clog the composition, is preferable. Of course, other coating tools can be used as long as they can efficiently coat the composition in the amount determined for each composition and can spray the composition to the desired particle size.
[0038] The spray gun for architectural coating materials having a diameter of 4 to 8 mm may be a lysine gun or a duraku gun, and the spray pressure is preferably 0.4 to 0.8 MPa. The spray gun for architectural coating materials having a diameter of 8 to 14 mm may be a tile gun or a stucco gun, and the spray pressure is preferably 0.3 to 0.7 MPa.
[0039] The present invention will be specifically described below with reference to examples and comparative examples. EXAMPLES
[0040] <Undercoating material composition> The emulsion consisted of 30 parts by weight of Acronal YJ6235D (solid content: 55%, glass transition temperature of resin: 6°C, copolymer of styrene and acrylic acid ester, product name, manufactured by BASF) as an acrylic resin emulsion, and 30 parts by weight of heavy calcium carbonate BF200S (average particle size D 50 10 parts by weight of calcium carbonate K-250 (average particle size D 50200 μm, Asahi Komatsu Co., Ltd., product name) and 35 parts by weight of Ti-PureR-960 (average particle size D 50 A primer composition was prepared by uniformly mixing and dispersing 2.5 parts by weight of 500 nm, product name, manufactured by Chemours, 1.0 part by weight of water-soluble cellulose ether hi-metolose 90SH-15000 (manufactured by Shin-Etsu Chemical Co., Ltd., product name) as a thickener, 1.5 parts by weight of Texanol CS-12 (manufactured by Chisso Corporation, product name) as a film-forming aid, 15 parts by weight of water, and a total of 5.0 parts by weight of a commercially available defoamer and dispersant for aqueous compositions.
[0041] <Paint finishing composition> The coating material finishing compositions of the examples and comparative examples were prepared according to the formulations in Table 1. In Table 1, the acrylic resin emulsion used was Acronal 7059 (solid content: 55%, glass transition temperature of resin: 30°C, copolymer of styrene, acrylic acid ester, and methacrylic acid ester, product name, manufactured by BASF), and the filler was silica sand powder #300 (average particle size D 50 25μm, Tochu Corporation, product name) was used, and the aggregate was Tohoku Silica Sand No. 7 (average particle size D 50 The straw A was made of refined straw (length: 30-50 mm, made by Murai Shoten, product name), the straw B was made of scum (length: 10-20 mm, made by Kinki Wall Materials Industry Co., Ltd., product name), the pigment was fine titanium oxide TTO-55(D) (primary particle diameter: 30-50 nm, made by Ishihara Sangyo Kaisha, Ltd., product name), the fine zinc oxide was FZO-50 (primary particle diameter: 21 nm, made by Ishihara Sangyo Kaisha, Ltd., product name), the general-purpose titanium oxide was Titan Haku R-820 (primary particle diameter: 260 nm, made by Ishihara Sangyo Kaisha, Ltd., product name), the thickener was water-soluble cellulose ether hi-metolose 90SH-15000 (made by Shin-Etsu Chemical Co., Ltd., product name), and the film-forming assistant was Texanol CS-12 (made by Chisso Corporation, product name). In addition, a defoamer and a dispersant were used as additives, which were appropriately selected from commercially available products for water-based compositions. These raw materials were uniformly mixed and dispersed to prepare the coating material finishing compositions of the examples and comparative examples.
[0042] [Table 1]
[0043] <Evaluation method> The following evaluations were carried out for the above-mentioned Examples and Comparative Examples. Unless otherwise specified, the preparation, curing and evaluation tests of test specimens were carried out in an environment of 23° C. and 50% RH.
[0044] <Design> On a flexible board (150 × 210 mm, thickness 10 mm) specified in JIS A 5430, water-based acrylic resin sealer JS-800 (solid content: 17.4% by weight, product name, manufactured by Aica Kogyo Co., Ltd.) was applied at a rate of 0.1 kg / m. 2 After drying, the undercoat composition was applied at a rate of 1.0 kg / m 2 Then, the coating material finishing compositions of the Examples and Comparative Examples were applied with a trowel in an amount of 2.5 kg / m 2 The coating was then applied to the test specimens, which were then cured for 24 hours. The coating was then observed and rated as ◯ if the straw was clearly visible, △ if the straw was slightly concealed but still had the overall appearance of a straw-like clay wall, and × if the straw was completely concealed.
[0045] <Base conformity> Two pieces of JIS A 5430-specified flexible board (100 × 100 mm, 10 mm thick) were butted together with their ends facing each other, and their backs were temporarily fixed with masking tape. A water-based acrylic resin sealer JS-800 (solid content: 17.4% by weight, Aica Kogyo Co., Ltd., product name) was applied to the surface at a rate of 0.1 kg / m. 2 After drying, the undercoat composition was applied at a rate of 1.0 kg / m 2 Then, the coating material finishing compositions of the Examples and Comparative Examples were applied with a trowel in an amount of 2.5 kg / m 2The coating was applied to the test piece and cured for 7 days to prepare a test piece. The masking tape on the back of the test piece was removed, and both ends of the test piece were pulled at 2 mm / min using a universal testing machine (manufactured by Instron Corporation) to measure the distance at which pinholes were generated in the coating film at the butted portion. The distance was evaluated as ◯ when it was 0.5 mm or more, and as × when it was less than 0.5 mm.
[0046] <Weather resistance> A JIS A 5430-specified flexible board (70 x 70 mm, thickness 8 mm) was used as the base, and a water-based acrylic resin sealer JS-800 (solid content: 17.4% by weight, product name, manufactured by Aica Kogyo Co., Ltd.) was applied in an amount of 0.1 kg / m. 2 After drying, the undercoat composition was applied at a rate of 1.0 kg / m 2 Then, the coating material finishing compositions of the Examples and Comparative Examples were applied with a trowel in an amount of 2.5 kg / m 2 The test specimen was prepared by applying the composition with a pH of 10.0 or less and curing it for 7 days. In order to make it easier to observe the color change, the coating composition was colored amber, and 100 parts by weight of the coating composition of the examples and comparative examples was mixed with AMJ8800 (red iron oxide-based water-based toner, Dainichi Seika Chemicals Mfg. Co., Ltd., product name): AMJ8150 (ochre-based water-based toner, Dainichi Seika Chemicals Mfg. Co., Ltd., product name): AMI9700 (carbon black-based water-based toner, Dainichi Seika Chemicals Mfg. Co., Ltd., product name) in a mixing ratio of 4:1:1, and 1 part by weight was added and stirred uniformly, and the above test specimen was prepared using this. Two test specimens were prepared, and one of them was subjected to a UV weather resistance tester (EYESUPER UV TESTER SUV-W161, metal halide lamp, Iwasaki Electric Co., Ltd.) for testing. The UV irradiation conditions were 24 hours of UV irradiation at a temperature of 50°C and a humidity of 50% RH, followed by 24 hours of non-UV irradiation at a humidity of 99% RH to allow the surface of the test specimen to condense, which constituted one cycle, for a total of 500 hours of testing. The color difference (ΔE) between the coating film after the test and another non-UV-irradiated coating film was measured using a colorimeter (CM-2600d, manufactured by Konica Minolta Sensing, Inc.), and ΔE of 1.0 or less was evaluated as ○, ΔE of more than 1.0 to 3.0 or less was evaluated as △, and ΔE of more than 3.0 was evaluated as ×.
[0047] <Stain resistance> A JIS A 5430-specified flexible board (80 x 265 mm, thickness 4 mm) was used as the base, and a water-based acrylic resin sealer JS-800 (solid content: 17.4% by weight, product name, manufactured by Aica Kogyo Co., Ltd.) was applied in an amount of 0.1 kg / m 2 After drying, the undercoat composition was applied at a rate of 1.0 kg / m 2 Then, the coating material finishing compositions of the Examples and Comparative Examples were applied with a trowel in an amount of 2.5 kg / m 2 The test specimens were prepared by applying the coating solution at a rate of 1000 μm and curing for 7 days. Two test specimens were prepared, one of which was installed vertically at an angle of 70 degrees to the horizontal plane. The lower end of a corrugated plate (wave width 32 mm, length 500 mm) installed at an angle of 10 degrees to the horizontal plane was placed at a height of 300 mm from the top of the coating surface of the test specimen, so that rainwater flowing down the bottom of the corrugated plate fell on the top of the coating film of the test specimen, and the rainwater flowed down to the bottom of the coating film of the test specimen under its own weight. Under these conditions, the test specimens were exposed outdoors for three months, and the color difference (ΔE) between the coating film part soiled by rainwater and the other test specimen coating film that was not exposed was measured using a colorimeter (CM-2600d, manufactured by Konica Minolta Sensing Co., Ltd.), and the color difference was evaluated as the stain resistance. Those with a ΔE of 1.0 or less were rated as ◯, those with a ΔE of more than 1.0 and less than 3.0 were rated as △, and those with a ΔE of more than 3.0 were rated as ×.
[0048] <Evaluation Results> The evaluation results are shown in Table 2.
[0049] [Table 2]
Claims
1. A composition comprising an acrylic resin emulsion, a filler, an aggregate, straw, a pigment, a thickener, and a film-forming aid, A coating finishing composition characterized in that the pigment contains fine particle titanium oxide and / or fine particle zinc oxide having a primary particle diameter of 10 to 100 nm, and the total amount of the fine particle titanium oxide and / or fine particle zinc oxide is 0.5 to 4.5 parts by weight per 100 parts by weight of the total composition.
2. 2. The coating material finishing composition according to claim 1, characterized in that the straw is contained in an amount of 0.01 to 10 parts by weight per 100 parts by weight of the total composition.
3. 3. The coating composition according to claim 1, wherein the length of the straw is 1 to 100 mm.
4. Apply a sealer on top of the base or on top of it and let it dry, then The undercoat material composition is characterized in that it contains an acrylic resin emulsion, a filler, an aggregate, a pigment, a thickener, and a film-forming aid, and the amount of the pigment is 0.5 to 5.0 parts by weight per 100 parts by weight of the composition, and is applied in an amount of 0.7 to 1.5 kg / m 2 Apply and let dry. On top of this, the coating material finishing composition according to any one of claims 1 to 3 is applied in an amount of 1.0 to 5.0 kg / m 2 A coating finishing method characterized by applying a coating material.
Citation Information
Patent Citations
Coating composition giving pattern like short-cut straw plastering fiber
JP1999302575A
Coating material containing colored straw, and wall material
JP2006037041A
